Assessment of the allelochemical activity and biochemical profile of different phenotypes of picocyanobacteria from the genus synechococcus - Konarzewska, Z. (2020)
Organisms belonging to Synechococcus sp. genera are observed in all freshwater, brackish, and marine waters of the world. They play a relevant role in these ecosystems, since they are one of the main primary producers, especially in open ocean. Eventually, they form mass blooms in coastal areas, which are potentially dangerous for the functioning of marine ecosystems. Allelopathy could be an important factor promoting the proliferation of these organisms. According to the authors’ best knowledge, there is no information on the allelopathic activity and allelopathic compounds exhibited by different Synechococcus sp. phenotypes. Therefore, the research conducted here aimed to study the bioactivity of compounds produced by three phenotypes of Synechococcus sp. by studying their influence on the growth, chlorophyll fluorescence, and photosynthetic pigments of eighteen cyanobacteria and microalgae species. We demonstrated that three different Synechococcus sp. phenotypes, including a phycocyanin (PC)-rich strain (Type 1; green strain) and phycoerythrin (PE)-rich strains containing phycoerythrobilin (PEB) and phycocyanobilin (PCB) (Type 2; red strain and Type 3a; brown strain), had a significant allelopathic effect on the selected species of cyanobacteria, diatoms, and green algae. For all green algae, a decrease in cell abundance under the influence of phenotypes of donor cyanobacteria was shown, whereas, among some target cyanobacteria and diatom species, the cell-free filtrate was observed to have a stimulatory effect. Our estimates of the stress on photosystem II (Fv/Fm) showed a similar pattern, although for some diatoms, there was an effect of stress on photosynthesis, while a stimulatory effect on growth was also displayed. The pigment content was affected by allelopathy in most cases, particularly for chlorophyll a, whilst it was a bit less significant for carotenoids. Our results showed that Synechococcus sp. Type 3a had the strongest effect on target species, while Synechococcus sp. Type 1 had the weakest allelopathic effect. Furthermore, GC-MS analysis produced different biochemical profiles for the Synechococcus strains. For every phenotype, the most abundant compound was different, with oxime-, methoxy-phenyl- being the most abundant substance for Synechococcus Type 1, eicosane for Synechococcus Type 2, and silanediol for Synechococcus Type 3a